Clinical and socio-behavioral correlates of tooth loss: a study of older adults in Tanzania - Åstrøm Anne N; Kida Irene A; Strand Gunhild V; Masalu Joyce R (BMC, 2006)
Abstract Background Focusing 50 year olds and above, this study assessed the frequency, extent and correlates of tooth loss due to various reasons. Frequency and correlates of posterior occluding support was also investigated. Method A cross-sectional household survey was conducted in Pwani region and in Dar es Salaam in 2004/2005. One thousand and thirty-one subjects, mean age 62.9 years participated in a clinical examination and completed interviews. Results The prevalence of tooth loss due to any reason was 83.5 %, due to caries 63.4% and due to other reasons than caries, 32.5%. A total of 74.9% had reduced number of posterior occluding units. Compared to subjects having less than 5 teeth lost due to caries, those with 5 or more lost teeth were more likely to be females, having decayed teeth, confirming dental attendance and to be among the least poor residents. Compared to subjects who had lost less than 5 teeth due to reasons other than caries, those who had lost 5 or more teeth were more likely to be of higher age, having mobile teeth, being males, being very poor and to disconfirm dental attendance when having problems. Predictors of prevalence of tooth loss (1 or more lost tooth) due to various reasons and reduced number of occluding units followed similar patterns of relationships. Conclusion The results are consistent with prevalence and extent of tooth loss due to caries and due to reasons other than caries being differently related to disease- and socio- behavioral risk indicators. Caries was the principle cause of tooth loss and molar teeth were the teeth most commonly lost.